(untitled) (Northern International Medical College Journal, 2017)
Background : Low utilization of routine postnatal care (PNC) is an important determinant of high maternal and neonatal mortality in Bangladesh. Objective : To determine the utilization of post-natal care services among the rural women in a selected area in Bangladesh. Methodology : During October 2015 to March 2016 a descriptive, cross-sectional study was carried out among 200 married women of reproductive age who had a live baby below 5years of age. Sample was selected purposively from village Islampur in Dhamrai Upzilla under Dhaka district. After taking informed consent data were collected by face to face interview using structured questionnaire. Results : The study revealed that 73.50% of the respondents utilized PNC services among them 55.10% took PNC for less than 3 times and 28.57% took PNC for more than 3 times during postnatal period. Most of them 86% were house wife; age between 25-30 years. About 35% respondents were educated up to secondary level and 31.5% were from middle economic group. In this study 79.50% respondents received Antenatal care and advice for Post-Natal Care (PNC) Source of information for PNC was 32.5% from health workers. Fifty nine percent respondents took PNC on combined decision of husband and wife. A significant number of respondents 61.91% received postnatal care at Upazilla Health Complex. Most of the respondents 73.47% found health care provider available on duty and good behavior were found by 72.11% respondents. Among respondents 62.59% attended Health Centre by walking. Only 59.86% respondents got free PNC service. Regarding importance of PNC 67.5% believed for healthy mother and 12.5% for healthy baby. Conclusions : Post Natal Care service utilization was satisfactory (73.50%) in the study area which is higher than the national figure (36%). The findings of the study clearly showed that female education, monthly household income, antenatal care utilization, distance of health center turned out important factors in determining the postpartum care utilization among the mothers. Availability and interaction with health care providers also affected the postpartum care utilization in the study population. Northern International Medical College Journal Vol.8(2) January 2017: 208-212